Design, synthesis and biological evaluation of inhibitors of cathepsin K on dedifferentiated chondrocytes. Issue 6 (15th March 2019) - Yuan, Xiao-Yu; Ren, Zhongyuan; Wu, Yuqing; Bougault, Carole; Brizuela, Leyre; Magne, David; Buchet, René; Mebarek, Saida
Graphical abstract: Abstract: Selective proteinase inhibitors have demonstrated utility in the investigation of cartilage degeneration mechanisms and may have clinical use in the management of osteoarthritis. The cysteine protease cathepsin K (CatK) is an attractive target for arthritis therapy. Here we report the synthesis of two cathepsin K inhibitors (CKIs): racemic azanitrile derivativesCKI-E and CKI-F, which have better inhibition properties on CatK than the commercial inhibitor odanacatib (ODN). Their IC50 values and inhibition constants ( Ki ) have been determined in vitro. Inhibitors demonstrate differential selectivity for CatK over cathepsin B, L and S in vitro, with Ki amounting to 1.14 and 7.21 nM respectively. We analyzed the effect of these racemic inhibitors on viability in different cell types. The human osteoblast-like cell line MG63, MOVAS cells (a murine vascular smooth muscle cell line) or murine primary chondrocytes, were treated either with CKI-E or with CKI-F, which were not toxic at doses of up to 5 µM. Primary chondrocytes subjected to several passages were used as a model of phenotypic loss of articular chondrocytes, occurring in osteoarthritic cartilage. The efficiency of CKIs regarding CatK inhibition and their specificity over other proteases were validated in primary chondrocytes subjected to several passages. Racemic CKI-E and CKI-F at 0.1 and 1 µM significantly inhibited CatK activity in dedifferentiated chondrocytes, even better than the commercial CatK inhibitor ODN. The enzymatic activity of other proteases such as matrix metalloproteinases or aggrecanases were not affected. Taken together, these findings support the possibility to design CatK inhibitors for preventing cartilage degradation in different pathologies.